Teaching about genocide : issues, approaches, and resources - Totten, Samuel 1949- Hrsg (Information Age Publ, 2004)
Educating about genocide, yes : but what kind of education? / Carol Rittner -- Issues of rationale : teaching about genocide / Samuel Totten -- The history of genocide : an overview / Paul R. Bartrop and Samuel Totten -- Wrestling with the definition of "genocide" : a critical task / Samuel Totten -- Defining genocide : issues and resolutions / Henry R. Huttenbach -- "Case studies" of genocide perpetrated in the twentieth century : the Armenian genocide / Richard G. Hovanissian -- The Soviet manmade famine in Ukraine / James Mace -- The Holocaust / Michael Berenbaum -- The Indonesian genocide of 1965-1966 / Robert Cribb -- The Bangladesh genocide / Rounaq Jahan -- The Burundi genocide / René Lemarchand -- The Cambodian genocide / Craig Etcheson -- The 1988 Anfal operations in Iraqi Kurdistan / Michiel Leezenberg -- Genocide in Bosnia / Eric Markusen -- The Rwanda genocide / René Lemarchand -- Instructional strategies and learning activities : teaching about genocide / Samuel Totten -- Conducting a comparative study of genocide : rationale and methodology / Henry R. Huttenbach -- Human rights, genocide, and social responsibility / William R. Fernekes and Samuel Totten -- Intervention and prevention of genocide : where there is the political will, there is a way / Samuel Totten -- Selected annotated bibliography : teaching about genocide / Samuel Totten